The tale of Despereaux [videorecording (DVD)] - Fell, Sam; Stevenhagen, Robert; Broderick, Matthew, 1962-; Hoffman, Dustin, 1937-; Watson, Emma, 1990-; DiCamillo, Kate (Universal ; Distributed by Universal Studios Canada, 2009)
After being banished from the kingdom of Dor for wanting to be a knight, Despereaux, a mouse with over-sized ears, sets off with his friend Roscuro on a quest to rescue a princess and save the kingdom from darkness.